2001
DOI: 10.4049/jimmunol.166.3.1601
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Molecular Factors Controlling Qa1-Mediated Protection of Target Cells from NK Lysis

Abstract: CD94/NKG2 receptors on mouse NK cells recognize the nonclassical class I molecule Qa1 and can deliver inhibitory signals that prevent NK cells from lysing Qa1-expressing cells. However, the exact circumstances under which Qa1 protects cells from NK lysis and, in particular, the role of the dominant Qa1-associated peptide, Qdm, are unclear. In this study, we examined in detail the lysis of Qa1-expressing cells by fetal NK cells that express CD94/NKG2 receptors for Qa1 but that lack receptors for classical class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…Although the cells used to identify this peptide, namely C1R cells, express very low levels of MHC class Ia molecules overall, they do express HLA-B35 at 60-fold reduced levels and HLA-Cw4 at normal levels (44), relative to the parental cell line. Peptides derived from the leader sequences of both of these proteins (VTAPRTVLL and VMAPRTLIL, respectively) have been shown to bind to Qa-1 b with a similar affinity to Qdm (8,9,21,39). However, these two MHC class Ia leader peptides were not detected in the extracts from MHC class I immunoprecipitates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the cells used to identify this peptide, namely C1R cells, express very low levels of MHC class Ia molecules overall, they do express HLA-B35 at 60-fold reduced levels and HLA-Cw4 at normal levels (44), relative to the parental cell line. Peptides derived from the leader sequences of both of these proteins (VTAPRTVLL and VMAPRTLIL, respectively) have been shown to bind to Qa-1 b with a similar affinity to Qdm (8,9,21,39). However, these two MHC class Ia leader peptides were not detected in the extracts from MHC class I immunoprecipitates.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these GroEL/Qa-1-reactive T cells cross-react with a peptide derived from the homologous murine protein, hsp60 (GMKFDRGYI), in a Qa-1-restricted fashion (35,36). These two peptides are not able to inhibit NK cell lysis of Qa-1-expressing target cells (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The alanine in P1 and P3 of the MRP7 peptide are in excellent agreement with amino acids that are accommodated by HLA-E as evidenced by the fact that the P1 and P3 residues of all leaderderived inhibitory peptides are also alanine. Although crystallographic studies indicate that the B pocket of HLA-E may be optimized for a P2 methionine, (10) the data presented here together with the observations from other groups using a soluble refolding assay, NK inhibition, and random peptide libraries clearly substantiate that leucine in P2 is also well-suited for both HLA-E and Qa-1-binding peptides that inhibit NK cell lysis (15,16,26). The presence of a positively charged amino acid within the middle region of an HLA-E-binding peptide is a key component of the sequence selectivity imposed by the HLA-E structure (10).…”
Section: Identification Of Novel Inhibitory Peptide Bound To Hla-ementioning
confidence: 51%
“…Qa-1 b is the murine MHC class Ib functional homologue of HLA-E and several reports have found that both molecules bind a nearly identical repertoire of leader-derived peptides (1)(2)(3)(12)(13)(14)(15)(16). Early studies using L cells transfected with the Qa-1 b -encoding gene T23 showed that the level of surface Qa-1 b is selectively increased following elevated temperature at 42°C (17).…”
mentioning
confidence: 99%